TALENT MANAGEMENT: REVIEW ARTICLE - Asrar Abdulzahra Ali; Alaulddin B. Jawad (Scholar Express Journals, 2022)
Talent management is one of the modern concepts that has attracted the attention of many researchers and writers, whether in the theoretical or applied fields, because of its great impact on the organization’s ability to attract scarce human resources and manage its performance, development and retention, which is an important factor in its success and for the purpose of identifying the content of Talent management will address the following paragraphs: Previous studies The concept of talent The historical development of talent management Entrances to talent management The importance of talent management
Keywords: human resources; talent management